Delay-Aware routing protocol for time-critical wireless sensor networks - Do, Duy Tan; Dang , Phuoc Hai Trang; Huynh, Thi Thu Hien; Le, Minh Thanh (Journal of Technical Education Science, 2019)
In this paper, we propose a distributed traffic-balancing routing protocol for large-scale wireless sensor networks to distribute traffic from sources to sinks effectively by utilizing the number of hops and the current queue size at one- and two-hop next neighbors to make routing decisions. Specifically, each node has a gradient field deciding a neighbor node to reach a sink. The gradient index of each node contains the distance cost from a source to a respective sink and traffic information from neighbor nodes. The presented algorithm considers the traffic of surrounding neighbors before forwarding packets to any sink using gradient search for routing in balance between optimal paths and possible congestion on the routes towards those sinks. This method leads to a trade-off between shortest paths and packet delay which is caused by congestion at overloaded nodes. Simulation results show that the proposed scheme effectively reduces the overall packet delay and improves throughput ratio with heavy traffic.